2020
DOI: 10.1186/s12887-020-2001-x
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-specific trends in respiratory outpatient visits and diagnoses at a tertiary pediatric hospital in China: a 10-year retrospective study

Abstract: Background: Respiratory infections are one of three leading causes of childhood mortality, and worldwide increase and recent plateau in childhood asthma has been reported. However, data on trends of respiratory diseases over long period of time is limited. This study aimed to determine the trends of respiratory disease outpatient visits (ROVs) and diagnoses (RODs) in one of the largest children's teaching hospitals in China between 2009 and 2018. Methods: A retrospective study based on routine administrative d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Children have a higher susceptibility to the adverse health effects of external factors due to their immature immune systems, their underdeveloped lung and metabolic systems, as well as high ventilation rates and mouth breathing, leading to an increased risk of impaired lung function and respiratory diseases [ 5 ]. A 10-year retrospective study started in 2009 based on one of the largest children’s teaching hospitals in China reported that bronchitis with a prevalence of 27.6%, pneumonia (18.5%), pneumonia affecting other systems (18.4%), and asthma and status asthmaticus (10.7%) were the top four most prevalent respiratory diseases and accounted for 75.2% of all recorded respiratory disease diagnoses [ 6 ]. It is reported that the prevalence of asthma in children increased from 0.91% in 1990 to 2.12% in 2010 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children have a higher susceptibility to the adverse health effects of external factors due to their immature immune systems, their underdeveloped lung and metabolic systems, as well as high ventilation rates and mouth breathing, leading to an increased risk of impaired lung function and respiratory diseases [ 5 ]. A 10-year retrospective study started in 2009 based on one of the largest children’s teaching hospitals in China reported that bronchitis with a prevalence of 27.6%, pneumonia (18.5%), pneumonia affecting other systems (18.4%), and asthma and status asthmaticus (10.7%) were the top four most prevalent respiratory diseases and accounted for 75.2% of all recorded respiratory disease diagnoses [ 6 ]. It is reported that the prevalence of asthma in children increased from 0.91% in 1990 to 2.12% in 2010 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each year, childhood respiratory infections significantly burden our healthcare system regarding staffing and resource utilization [ 1 , 2 ]. Statistics from one of the largest children’s hospitals in China showed that bronchitis and pneumonia are the leading respiratory diseases in outpatient during the decade [ 3 ], of which pneumonia has been the leading cause of death under 5 years old worldwide for the past three decades. It is estimated that 1.2 million children under the age of five die of pneumonia yearly [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [5] reported a prevalence of 10.2% for asthma, 54.1% for rhinitis, and 22.5% for eczema in Shanghai, China. A retrospective study conducted in a tertiary pediatric hospital in Shanghai reported that asthma and rhinitis accounted for 20% of respiratory outpatient visits [6]. ADs are often associated with various comorbidities, which have a significant impact on health outcomes [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%